Comparison of superior airway dimensions and cephalometric anatomic landmarks between 8-12-year-old children with obstructive sleep apnea and healthy children using CBCT images - Farzad Emsaeili; Amirhouman Sadrhaghighi; Mahnaz Sadeghi-Shabestari; Parastou Nastarin; Aliakbar Niknafs (Tabriz University of Medical Sciences, 2022)
Background. The etiology of obstructive sleep apnea (OSA) syndrome in children significantly differs from adults. In previous studies, only some of the indices have been investigated using CBCT. This study compares all the measurable indices of airway dimensions and anatomical cephalometric landmarks between children with OSA and healthy ones using cone-beam computed tomography (CBCT). Methods. Dimensions of the airway and cephalometric values were measured on CBCT scans of 50 children aged 8-12 (25 patients with OSA and 25 healthy subjects) and then compared between the two groups. The results of this study were analyzed with independent t test using SPSS 17 at a significance level of P<0.05. Results. Area, length, volume, anteroposterior length, and size of the upper airway in subjects with OSA were lower than those in healthy children, while the average values of SNA, SNB, and ANB in the OSA group were higher than those in the healthy group (P=0.366, P=0.012, and P=0.114, respectively). Also, BaSN, PNS/AD1, and PNS/AD2 measurements in subjects with OSA were lower than healthy subjects (P=0.041, P=0.913, and P=0.015, respectively). In addition, the width and anteroposterior length of the upper airway, SNB, BaSN, PNS/AD1, and PNS/AD2 indices were significantly different between the healthy group and those with OSA (P<0.05). Conclusion. Reduced upper airway dimensions, adenoid tissue enlargement, and cranial base flexion might play an important role in OSA development in children. However, most skeletal variables, such as the anteroposterior relationship of jaws and jaw rotation, were not significantly different between the two groups.